Demography of the George River Caribou Herd: Evidence of Population Regulation by Forage Exploitation and Range Expansion - Messier, F.; Huot, J.; Le Henaff, D.; Luttich, S. (ARCTIC, 1988)
The George River caribou herd in northern Quebec/Labrador increased from about 5000 animals in 1954 to 472,200 (or 1.1 caribou/km) prior to the 1984 calving season. The range used by the herd expanded from 160,000 to 442,000 sq km for the period 1971-84. The exponential rate of increase (r) was estimated at 0.11 in the 1970s. Calf:female ratio in autumn was relatively constant (x=0.52) from 1973 to 1983, but decreased to about 0.39 in 1984-86. The harvest rate was relatively low in the 1970s (about 3%/y), but seemingly increased in the mid-1980s to 5-7% as a result of more liberal regulations and a greater impetus to exploit caribou for subsistence. The cumulative impact of lower calf recruitment and more intensive hunting may have appreciably depressed the growth rate of the herd in 1984-86. A greater year-round competition for food resources and a greater energy expenditure associated with range expansion are presented as probable regulatory factors for the George River herd. It is argued that the nature of caribou-habitat interactions in continental regions generate long-term fluctuations in caribou numbers if human exploitation remains low. At present, wolf predation does not appear to be an important mortality factor capable of regulating the George River herd.Key words: caribou, population regulation, food limitation, northem Quebec, Labrador, wolf predation Mots clés: caribou, régulation de la population, limitation de la nourriture, nord du Québec, Labrador, prédation des loups